Market reaction before and after stipulation of presidential regulation point 55 in 2019 - Dananjaya, Ida Bagus Gede; Sedana, Ida Bagus Panji (International research journal of management, IT and social sciences, 2020)
The purpose of this study is to examine the capital market reaction to the adoption of Perpres no. 55 2019 with abnormal return and trading volume activity as indicators. This study uses 10 companies listed in the automotive subsector and components in the Indonesia stock exchange in the period of 5 days before and after the adoption of Presidential Decree No. 55 of 2019. The analysis technique used in this study is the Wilcoxone Signed Rank Test and the Paried Sample t-test test. Wilcoxone Signed Rank Test results prove that there are differences in the average negative abnormal return before and after the stipulation of Presidential Regulation no. 55 2019 based on the results of these tests it can be concluded that investors consider the information as bad news (bad news). Paried Test Results in The t-test sample proves that there is no difference in the average trading volume activity before and after the stipulation of Presidential Regulation no. 555 in 2019 based on these tests it was concluded that it did not trigger stock movements in the capital market that affect the supply and demand of existing shares in the automotive and component sub sector shares.